2012
DOI: 10.1007/s11250-012-0247-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of equine influenza virus in two geographical regions of Pakistan

Abstract: Influenza viruses are circulating in equine species and continuous surveillance is needed to keep check on any future outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Ultimately, genetic and antigenic re-assortments chance increases, as also reported previously (Guan et al, 1999;Perglione et al, 2016). Notably, antibodies against viruses from poultry origin (H1N1) in equines have also been reported in the same study region in past (Sajid et al, 2013). Consequently, it can be seen that the novel reassortant equine/Pakistan/16 viruses were circulating in different equine species in KP province of Pakistan during 2015-2016 giving rise to a countless uncertainty for the present ecosystem of EIV and other influenza A virus in Northern regions of Pakistan.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Ultimately, genetic and antigenic re-assortments chance increases, as also reported previously (Guan et al, 1999;Perglione et al, 2016). Notably, antibodies against viruses from poultry origin (H1N1) in equines have also been reported in the same study region in past (Sajid et al, 2013). Consequently, it can be seen that the novel reassortant equine/Pakistan/16 viruses were circulating in different equine species in KP province of Pakistan during 2015-2016 giving rise to a countless uncertainty for the present ecosystem of EIV and other influenza A virus in Northern regions of Pakistan.…”
Section: Discussionsupporting
confidence: 77%
“…KP is comprised of many of coldest regions in the country located at the border with Afghanistan. EI for the first time was reported in 2013 in Pakistan (Sajid et al, 2013), detecting and reporting several seropositive cases for H3N8, H7N7 and H1N1 without a successful isolation of EI viruses. Here we isolated the virus for the first time from horses and equines during the current outbreak in the province of Khyber Pakhtunkwa, in the extreme north of Pakistan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several serological surveillance studies for EIV have been conducted in many regions in the world . In this study, we reported the seroprevalence of horses to the H3N8 serotype of EIV in the Eastern and Central Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, other species of equine have been evaluated such as donkeys, mules and ponies. It has been recorded that prevalence of EI among ungulates in Pakistan is around 12% [13], while in Turkey is around 9.4% [1].…”
Section: Discussionmentioning
confidence: 99%